A Remorin from Nicotiana benthamiana Interacts with the Pseudomonas Type-III Effector Protein HopZ1a and is Phosphorylated by the Immune-Related Kinase PBS1 - Albers, Philip; Üstün, Suayib; Witzel, Katja; Kraner, Max; Börnke, Frederik (Molecular Plant-Microbe Interactions, 2019)
The plasma membrane (PM) is at the interface of plant–pathogen interactions and, thus, many bacterial type-III effector (T3E) proteins target membrane-associated processes to interfere with immunity. The Pseudomonas syringae T3E HopZ1a is a host cell PM-localized effector protein that has several immunity-associated host targets but also activates effector-triggered immunity in resistant backgrounds. Although HopZ1a has been shown to interfere with early defense signaling at the PM, no dedicated PM-associated HopZ1a target protein has been identified until now. Here, we show that HopZ1a interacts with the PM-associated remorin protein NbREM4 from Nicotiana benthamiana in several independent assays. NbREM4 relocalizes to membrane nanodomains after treatment with the bacterial elicitor flg22 and transient overexpression of NbREM4 in N. benthamiana induces the expression of a subset of defense-related genes. We can further show that NbREM4 interacts with the immune-related receptor-like cytoplasmic kinase avrPphB-susceptible 1 (PBS1) and is phosphorylated by PBS1 on several residues in vitro. Thus, we conclude that NbREM4 is associated with early defense signaling at the PM. The possible relevance of the HopZ1a–NbREM4 interaction for HopZ1a virulence and avirulence functions is discussed.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Bacterial pathogenesis; Defense signaling pathways; Effectors; Elicitors; HopZ1a; MAMPs; PAMPs; PBS1; Pseudomonas syringae; Remorin; Type-3 secretion